1991
DOI: 10.1104/pp.95.1.337
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Directly Inhibits Foliar Gas Exchange in Glycine max

Abstract: Gas exchange of individual attached leaves of soybean, Glycine max (L.) Merr cv Davis, was monitored during exposure to exogenous ethylene (C2H4) to test the hypothesis that the effects of C2H4 on net photosynthesis (PN) and stomatal conductance to H20 vapor (g8) are direct and not mediated by changes in leaf orientation to light. Leaflets were held perpendicular to incident light in a temperature-controlled cuvette throughout a 5.5 hour exposure to 10 microliters per liter C2H4. Declines in both PN and g, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 15 publications
(46 reference statements)
1
26
0
Order By: Relevance
“…Christmann and Fremzel (1997) suggested that acceleration of needle senescence is related to hormone balance between ethylene and indole-3-acetic acid. Ethylene also has an effect in decreasing the gl (Gunderson and Taylor 1991;Willmer and Fricker 1996). Under experimental conditions, Kobayashi et al (2002) showed close relationships between ethylene emission from needles and declines in Pn and gl when the rate of 路OH photoformation in morning dew was high on the needle surface of pine seedlings.…”
Section: Physiological Relationshipsmentioning
confidence: 95%
“…Christmann and Fremzel (1997) suggested that acceleration of needle senescence is related to hormone balance between ethylene and indole-3-acetic acid. Ethylene also has an effect in decreasing the gl (Gunderson and Taylor 1991;Willmer and Fricker 1996). Under experimental conditions, Kobayashi et al (2002) showed close relationships between ethylene emission from needles and declines in Pn and gl when the rate of 路OH photoformation in morning dew was high on the needle surface of pine seedlings.…”
Section: Physiological Relationshipsmentioning
confidence: 95%
“…Although the role of ethylene in stomatal behaviour has been suggested, its effect in this process seems rather contradictory (Acharya & Assmann 2009;Wilkinson & Davies 2010). In some species, ethylene induces stomatal opening and/or inhibits ABA-induced stomatal closure, or induces stomatal sensitivity to stresses/cues in which ABA is the normal signal for the given stomatal response (Madhavan et al 1983;Levitt et al 1987;Merritt et al 2001;Mills et al 2009;Benlloch-Gonza麓lez et al 2010), whereas in other species it induces closure (Pallas & Kays 1982;Giulivo 1986;Tissera & Ayres 1986;Gunderson & Taylor 1991;Young et al 2004;Desikan et al 2006;He et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Merr. ), mustard (Brassica juncea L.), and cotton [40]- [43]. A relation between decreased photosystem I and II activity to increased proteolysis and decreased chlorophyll content was found by using ethephon-treated isolated chloroplasts [44].…”
Section: Discussionmentioning
confidence: 99%